BISNIS DI BALIK UPACARA KEMATIAN ETNIS TIONGHOA DI SURABAYA, 1967 – 1998 - Olivia Daisiprima Santoso; Shinta Devi ISR (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2019)
This article discusses the role of service providers in the funeral rituals for the execution of death rituals among ethnic Chinese in Surabaya between 1967 and 1998. Business in death rituals is a business born out the necessities among the ethnic Chinese to conduct death rituals. Businesses in death rituals for ethnic Chinese in Surabaya grew in the New Order era. Aside from due to the implementation of the Presidential Instruction 14/ 1967, the growth of this business was also due the shifts in meanings given to the ethnic Chinese death rituals. The existance of the service providers in the funeral rituals eventually pushed the changes in the meanings and executions of the rituals among ethnic Chinese. The whole rituals which were voluntarily in nature before became more commercialized now. Death rituals and the business in funeral ritual behind them became events to show social and economic status of the grieving famiy.  Keywords: Death ritual, Chinese ethnic, business, Surabaya